Pengaruh Komunikasi Internal dan Kemampuan Sumber Daya Manusia Terhadap Efektivitas Kerja Pegawai PG Modjopanggoong Tulungagung - Nurdyansah Romadon (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2022)
This study aims to find out how much influence the Internal Communication and Human Resources Ability on the Work Effectiveness of PG Modjopanggoong Tulungagung employees. The benefits of this research can increase employee awareness about the importance of communication within the company and the ability of human resources to improve employee effectiveness. This research method uses quantitative methods using a causal approach or cause and effect using questionnaires, interviews and direct observation on the object of research. This research was conducted at PG Modjopanggoong Tulungagung jl. Kawi, Cuwini Sidorejo, Kauman subdistrict, Tulungagung Regency. The results of this study indicate that (1) Internal communication partially influences the work effectiveness of PG Modjopanggoong Tulungagung employees, (2) The ability of Human Resources partially influences the work effectiveness of PG Modjopanggoong Tulungagung Employees, (3) Internal Communication and Human Resource Capability have influence simultaneously on the Work Effectiveness of PG Modjopanggoong Tulungagung Employees. Keywords: Internal Communication; Human Resource Capability; Work Effectiveness